Respuesta :

~ Simplifying

4x + -3 = 2(2x + -1)

~ Reorder the terms:

-3 + 4x = 2(2x + -1)

~ Reorder the terms:

-3 + 4x = 2(-1 + 2x)

-3 + 4x = (-1 * 2 + 2x * 2)

-3 + 4x = (-2 + 4x)

~ Add '-4x' to each side of the equation.

-3 + 4x + -4x = -2 + 4x + -4x

~ Combine like terms: 4x + -4x = 0

-3 + 0 = -2 + 4x + -4x

-3 = -2 + 4x + -4x

~ Combine like terms: 4x + -4x = 0

-3 = -2 + 0

-3 = -2

~ Solving

-3 = -2

~ This equation is invalid, the left and right sides are not equal, therefore there is no solution.

ACCESS MORE